Desarrollo de una colección de indumentaria casual femenina a partir del corset de 1990 - Chimbay Yanza, Sonnia Del Pilar (2024)
The present research project was carried out with the objective of developing a collection of women's casual clothing for women in the city of Ambato through the analysis of the corset from the 1990s. A qualitative methodology was used, using techniques such as observation, interview and the focus group. In the first instance, observation was used to collect key information about the characteristics and preferences of Ambateña women between 20 and 36 years old in relation to their tastes and clothing choices. This approach facilitated a deep understanding of the consumer trends and behaviors of women in Ambato. Interviews were then conducted to gather detailed opinions on corset and casual clothing, providing a clear insight into their perceptions and expectations of these garments. The feedback obtained was crucial to adjust and improve the design proposals. Finally, an exhaustive analysis of the nine areas of design was carried out, a fundamental tool for understanding and segmenting the target audience. Based on the results of the diagnosis, a collection of women's casual clothing was designed based on the corset of the 90s, based on the 9 areas of design, focusing on creating outfits that reflect the preferences and styles of Ambateña women. Although six outfits were planned, three materialized: economical, trendy and basic, incorporating elements inspired by the corset aesthetic reinterpreted in a contemporary way.